1986
DOI: 10.2134/agronj1986.00021962007800010020x
|View full text |Cite
|
Sign up to set email alerts
|

A Nitrogen and Water Response Surface for Sprinkler‐Irrigated Broccoli1

Abstract: Farmers typically apply large amounts of both N and water in commercial vegetable production. As costs of both inputs increase, and with mounting concern over nitrate leaching and non-point source water pollution, the need for information on optimal management of both resources grows. We investigated the combined effects of five N application rates (0, 87, 190, 2SS, and 331 kg ha-1 ) and a continuous irrigation variable (1.14 to 32.9 em of water, or O.OS to 1.52 times net pan evaporation) applied by a line-sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…(1 reported by Sanchez et al (1996) but was lower than the rates of 380 to 558 kg N ha (1 reported in other studies (Greenwood et al 1980;Beverly et al 1986;Zebarth et al 1995;Thompson et al 2002). In some previous studies, yield increased to the maximum rate of nitrogen applied (180 to 270 kg N ha…”
Section: T Hamentioning
confidence: 80%
See 1 more Smart Citation
“…(1 reported by Sanchez et al (1996) but was lower than the rates of 380 to 558 kg N ha (1 reported in other studies (Greenwood et al 1980;Beverly et al 1986;Zebarth et al 1995;Thompson et al 2002). In some previous studies, yield increased to the maximum rate of nitrogen applied (180 to 270 kg N ha…”
Section: T Hamentioning
confidence: 80%
“…Optimal yields of broccoli (Brassica oleracea L. italica Plenck) have been reported with nitrogen rates ranging from 112 to 450 kg N ha (1 , depending on the production system and timing of nitrogen application (Cutcliffe et al 1968;Letey et al 1983;Beverly et al 1986;Shattuck and Shelp 1987;Zebarth et al 1995;Sanchez et al 1996; Thompson et al 2002). Currently, the Ontario Ministry of Agriculture, Food and Rural Affairs (OMAFRA) recommends a nitrogen application for broccoli totalling 130 kg N ha…”
mentioning
confidence: 99%
“…This differed from 2002, when at 14 d after planting, the rate of DM accumulation increased with high nitrogen rates but at 56 d after planting, the rate of DM accumulation was highest in the 0 kg N ha (1 plots. Magnifico et al (1979), Beverly et al (1986) and Bowen et al (1999) reported a similar pattern in DM accumulation over time, although values for DM varied among studies.…”
Section: Plant Growth and Tissue Nitrogen Analysismentioning
confidence: 81%
“…(1 (Cutcliffe et al 1968;Letey et al 1983;Beverly et al 1986;Shattuck and Shelp 1987;Zebarth et al 1995;Sanchez et al 1996;Thompson et al 2002a). Bakker et al (2009) applied seven rates (0 to 400 kg N ha…”
mentioning
confidence: 99%
“…In most studies that included rates up to 336 kg N ha -1 , the response was positive and linear or quadratic (Cutcliffe et al 1968;Cutcliffe et al 1971;Hipp 1974;Letey et al 1983;Beverly et al 1986;Kowalenko and Hall 1987b;Shattuck and Shelp 1987;Tremblay 1989), although two studies found minimal or no yield response to N fertilization (Bracy et al 1995;Kahn et al 1991). In studies that included higher N rates (Greenwood et al 1980;Zebarth et al 1995) or low soil moisture (Beverly et al 1986), a maximum yield response was found beyond which yield declined with additional N applied. The actual yields produced in response to N fertilization differed greatly among these studies.…”
mentioning
confidence: 99%